HOTS (Higher Order Thinking Skill) Based Monopoly Development as Learning Media for Animal and Food Materials - Rischa Dwi Arianti; Arfilia Wijayanti; Filia Prima Artharina (Jurnal Sekolah Dasar, 2020)
This research model uses several stages, namely the analysis phase, the design phase, the development stage, the implementation phase, the evaluation stage. The results showed the difference in class average between classes using media and not using monopoly media based on HOTS (Higher Order Thinking Skill). This is evidenced by the results of the t-test in which the number of t arithmetic (3,590)> ttable (1,708). So the result is effectiveness in the use of HOTS (Higher Order Thingking Skill) based animal and food material monopoly in grade IV SD 01 Kalicari.